Strategi Penguatan Pemahaman Kader PKK Desa Karangkamiri Melalui Kegiatan Sarasehan Bina Keluarga - Dede Nurul Qomariah; Fahmi Ihsanudin Iskandar; Eva Mustikasari; Naely Kamilatul Azizah; Siti Patimah; Irpan Ilmi; Asep Saepurrohman (Jurnal Masyarakat Mengabdi Nusantara, 2023)
The strategy of strengthening the understanding of PKK cadres in Karangkamiri Village through family development workshops aims to increase knowledge and provide reinforcement for PKK cadres regarding family development in carrying out their roles and functions in society. The method of implementing community service is carried out through problem identification, solutions offered, implementation of workshop activities, interviews, and achievement targets. This service was carried out in Karangkamiri Village, Langkaplancar District, Pangandaran Regency in March 2023. The output targets to be achieved are: equality and strengthening the perceptions of PKK cadres in efforts to build families. This strategy is expected to be able to support PKK cadres in carrying out their duties in the community, especially regarding efforts that can be made by PKK cadres in protecting the families around them. The conclusion is that the PKK cadres are very enthusiastic and welcome the workshop activities. They hoped that there would be a follow-up to the workshop activities, especially those that were implemented in the field on the knowledge gained during the workshop activities. So that in carrying out their duties in fostering families in Karangkamiri Village, they can be maximized.